The accidental city : improvising New Orleans - Powell, Lawrence N. (Harvard University Press, 2012)
Chronicles the history of the city from its being contended over as swampland through Louisiana's statehood in 1812, discussing its motley identities as a French village, African market town, Spanish fortress, and trade center.